Effect of Napier silage on milk production of Holstein Friesian Crossbred Cow - Habib, MAA; Akbar, MA; Khandaker, ZH (Bangladesh Journal of Animal Science, 2022)
This work aspired to evaluate the quality of different types of silage on milk production made from whole napier grass, napier stem, and napier leaf. Napier grass (Pennisetum Purpureum) was harvested at 70 days of age and made into three types of silage in three different silo pits under proper anaerobic conditions for 45 days. A feeding program of 60 days duration was designed on nine (9) lactating (110-140 days after calving) Holstein Friesian crossbred dairy cows of 2nd parity (age 6-7 years, live weight 500±5 kg). The cows were divided into 3 groups and assigned to 3 dietary treatments, basal ingredients with whole napier grass silage (T1), basal ingredients with chopped napier leaf silage (T2), and basal ingredients with napier stem silage (T3). After ensiling, it was found that napier stem silage possesses the highest pH value indicating low-quality silage whereas napier leaf silage possesses the lowest pH value. The pH value of whole napier grass silage was slightly higher than that of napier leaf silage. Concentrations of CP and NH3-N were highest in napier leaf silage and lowest in napier stem silage. The CP value was almost similar in whole napier grass silage and napier leaf silage but the NH3-N value of whole napier grass silage was lower than that of napier leaf silage. Among the three groups, the cows of napier leaf silage group gave significantly (P<0.05) higher milk yield than the cows of whole napier grass and napier stem silage group. On the other hand, the cows of napier stem silage group gave significantly (P<0.05) lower milk yield than the cows of whole napier grass and napier leaf silage group. It can be concluded that napier leaf and whole napier grass silage are comparatively better than napier stem silage in respect to milk production of dairy cows. Bangladesh Journal of Animal Science, 51 (2): 62-67.